Finite element analysis of dental structures: the role of mandibular kinematics and model complexity - Özcan, Canan; Lestriez, Philippe; Özcan, Mutlu; Josset, Yannick (Frontiers in Dental Medicine, 2024)
Introduction This study observed the consequences of integrating mandibular kinematics in maxillary and mandibular teeth contact in a finite element analysis (FEA), and investigate the level of simplification of the dental models in FEA. The purpose of this study was to compare the results of finite element analysis obtained from simple to more complex dental models incorporating mandibular motion during loading phase. Methods Six models were generated for this study. The simplest models consisted of only the crown of the tooth and an antagonist tooth with either the same properties or rigid body properties while the subsequent models incorporated the root of the study tooth and the surrounding bone. The most complex model involved the hyperelastic ligament and the other anatomical elements of the tooth and surrounding bone. Mandibular movement data recorded with the Modjaw® system (Modjaw-Technologie) were used to bring the teeth into contact and generate the loading in all models where the stresses exerted on tooth structures during the chewing process were evaluated. Results von Mises stress and the shear stress obtained in all models, exceeded the ultimate compression strength of the materials, except for the model with the hyperelastic periodontal ligament. The forces applied to the tooth were extremely different depending on the addition or removal of anatomical elements despite the systematic study of the same teeth. Discussion The inclusion of mandibular kinematics in the finite element analysis requires the modelling of a complex dental model as simplification generated an overestimation of the forces and stresses on the structures. Finite element dental models allow for the observation and prevention of restorative failures by numerical methods but misinterpretations caused by poorly designed models have clinical implications on estimating performance of dental restorations.